1877 Dakota Terr. Rev. Codes 794, § 456 - (:unkn) unknown (My University, 1877)
Penal Code, ch. 38, § 456: Prohibited the carry of any slungshot or weapon of similar kind. Violators guilty of a felony.
Keywords: CARRY - NON-GUN ARMS